Media Review - Howéll, Michael W. (Teaching History: A Journal of Methods, 1985)
Article published in Teaching History by Howéll. Film review of Danton, directed by Andrzej Wajda, Gaumont-Film Polski TF1 Films Production-S.F.P.C., 1982.